Analisis Hasil Belajar Matematika Siswa dalam Penerapan Kurikulum Merdeka di UPTD SMP Negeri 4 Gunungsitoli Utara - Jupi Yarman Lase; Sadiana Lase; Yulisman Zega; Yakin Niat Telaumbanua (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The Merdeka Curriculum is a recent initiative in Indonesia's education reform aimed at granting greater autonomy to schools and teachers in designing the learning process tailored to students' needs. Specifically, the Merdeka Curriculum is a government-driven process designed to create an environment that encourages students' active participation in learning, particularly in mathematics education. This process also involves active student engagement and reflects the outcomes of the learning experience. Student learning outcomes refer to the abilities acquired through educational activities and serve as quantitative indicators of post-learning evaluation. This study was conducted at UPTD SMP Negeri 4 Gunungsitoli Utara, specifically in Grade VIII. The research design is a qualitative descriptive study aimed at analyzing and describing student learning outcomes with respect to the implementation of the Merdeka Curriculum. Analysis of test results, which were administered to assess students' understanding of exponentiation concepts, revealed an average score of 65.74, with a mastery percentage of 70.37% and a non-mastery percentage of 29.63%. The student learning outcomes under the Merdeka Curriculum also show significant variation, depending on the preparedness of schools and teachers for implementing this curriculum.